SELECTION OF SOME DESIGN PARAMETERS OF A THERMAL FUEL FLOWMETER TO REDUCE MEASUREMENT ERROR - Ильченко, Андрей (SWorldJournal, 2021)
The article analyzes the influence of some design parameters of a thermal flow meter on its radial and axial heat fluxes in the tube (tube diameter, heater diameter and their ratio, thermal conductivity of the tube material). The ratios of the tube diamet